The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1111/j.1399-6576.1995.tb04219.x
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic paravertebral analgesia

Abstract: Thoracic paravertebral nerve blockade, although once widely practised, has now only a few centres which contribute to the literature. Data production has, however, continued and this review correlates this new information with existing knowledge. Its history, taxonomy, anatomy, indications, techniques, mechanisms of analgesia, efficacy, contraindications, toxicity, side effects and complications are reviewed. Thoracic paravertebral analgesia is advocated for surgical procedures of the thorax and abdomen, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 70 publications
2
47
1
Order By: Relevance
“…We point out that severe complications can be as high as 5% with the blind traditional paravertebral technique. 7,20 In this report, we suggest that utilizing ultrasoundguidance will further simplify and significantly improve the lamina approach described by Pfeiffer. Ultrasound imaging of the vertebral lamina is easy and reproducible.…”
Section: Discussionmentioning
confidence: 91%
“…We point out that severe complications can be as high as 5% with the blind traditional paravertebral technique. 7,20 In this report, we suggest that utilizing ultrasoundguidance will further simplify and significantly improve the lamina approach described by Pfeiffer. Ultrasound imaging of the vertebral lamina is easy and reproducible.…”
Section: Discussionmentioning
confidence: 91%
“…[5] The technique provided good operative anesthesia for major chest wall procedures as well as good postoperative analgesia. [6] Benefits include, reduction in postoperative nausea and vomiting and potential for ambulatory discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Although accidental pleural puncture is rare, [10] paravertebral block is still considered potentially dangerous by many anesthetist. [5] Using ultrasound to visualize anatomical landmarks, it will be possible to improve the safety of the block. Ultrasound imaging not only helps to determine needle insertion sites, but also provides information about the depth to the paravertebral space.…”
Section: Discussionmentioning
confidence: 99%
“…Pusch et al reported effective anaesthesia with single injection of high volume of bupivacaine in TPVB for breast lump excision and mastectomies with axillary clearance [4][5][6]. Richardson et al suggested TPVB is a safe and effective technique and should be considered as an ideal alternative to general anesthesia for unilateral thoracic surgeries [7,8]. LA like bupivacaine 0.0625% or ropivacaine 0.2% at the rate of 3-10 ml/hour in infusion form are found very effective in providing post operative analgesia [9].…”
Section: Discussionmentioning
confidence: 99%